MANAJEMEN PEMBELAJARAN KIMIA DENGAN MENERAPKAN MODEL KOOPERATIF TIPE GROUP INVESTIGASI BERBASIS PBL (PROJECT BASED LEARNING) DI MA - Yunitasari Yunitasari (UNIVERSITAS BENGKULU, 2017)
The purpose of this study are: to determine the application of chemical learning management by applying the model of cooperative-type Group Investigation Based PBL (Project Based Learning) can improve the readiness and student learning outcomes XII class IA Madrasah Aliyah Public 2 Bengkulu City. The method used in this research is a class act. The data collection technique is a test result of learning and observation of teaching and learning. Results of the study are: student learning readiness increased from cycle 1 to cycle 2 that is 75 to 87.5, the average value of grade increased from 72.82 into 86.00, completeness class rose from 64.70% to 91.17%.